Gestión de servicios en el Spa D Normi ubicado en el cantón Baba, periodo 2024. - Castillo Acosta, Dixy Nallely (2025)
This case study called Service Management in the Spa D Normi located in the canton Baba, period 2024, focuses on the problems that the spa has presented such as the lack of training of its staff in new trends in the modern market, the lack of customer loyalty, the high demand of competitors which negatively affects the company. In addition, this study is related to the research line: Financial, Administrative, Tax, Audit and Control Management and is framed with the Marketing and Commercialization subline. The main objective of this research is to analyze the service management at Spa D Normi in the period 2024, by using research techniques to identify the factors that influence customer satisfaction and loyalty. In this context, the techniques used are the EFI Internal Factors Matrix and the customer survey, in which the results reflect dissatisfaction on the part of customers with respect to the services in terms of long waiting times, the absence of an appointment scheduling system, this leads to the implementation of strategies that will allow them to improve their services and remain competitive in the market. In conclusion, in order for D Normi Spa to improve its image and keep its customers satisfied, it must pay attention to the areas identified by the research techniques such as the implementation of an appointment program, the development of a loyalty program and training staff in new trends.